Odpowiedzi

2010-03-05T21:44:43+01:00
A)√(3⁻²)=√(1/9)=1/3
b)(√3)⁻²=1/3
c)√(5⁻⁴)=5⁻²=1/25
d)(√5)⁴=5²=25
e)√(6⁻⁸)=1/6⁴=1/1296
f)√((-6)⁸)=(-6)⁴=1296
g)(√11)⁴=11²=121
h)√(11⁻⁴)=11⁻²=1/121
2010-03-05T22:51:19+01:00
A)
√(3⁻²)=√(1/9)=⅓
b)
(√3)⁻²=⅓
c)
√(5⁻⁴)=5⁻²=1/25
d)
(√5)⁴=5²=25
e)
√(6⁻⁸)=1/6⁴=1/1296
f)
√((-6)⁸)=(-6)⁴=1296
g)
(√11)⁴=11²=121
h)
√(11⁻⁴)=11⁻²=1/121
2010-03-06T00:15:01+01:00
A)√3⁻²=3⁻¹=1/3
b)(√3)⁻²=3⁻¹=1/3
c)√5⁻⁴=25⁻¹=1/25
d)(√5)⁴=25
e)√6⁻⁸=6⁻⁴=1/1296
f)√(-6)⁸=6⁴=1296
g)(√11)⁴=11²=121
h)√11⁻⁴=11⁻²=1/121